INFLUENCE EMPLOYEE ENGAGEMENT, CULTURE ORGANIZATION AND MOTIVATION WORK TO SATISFACTION WORK EMPLOYEES AT PT. PAWNSHOP PONOROGO - Putri, Shintia Nanda; Widhianingrum , Wahna; Wijianto, Wijianto (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
General Background: Effective human resource management is essential for organizational growth, particularly in fostering employee job satisfaction. Specific Background: Employee engagement, organizational culture, and work motivation are widely recognized as key factors influencing job satisfaction, yet their specific impacts may vary across organizations. Knowledge Gap: While previous studies have explored these variables, limited research has focused on their combined effect within the context of PT Pegadaian Ponorogo. Aims: This study aims to determine the partial and simultaneous effects of employee engagement, organizational culture, and work motivation on employee job satisfaction at PT Pegadaian Ponorogo. Results: The research, conducted using a quantitative approach with a population of 74 employees, reveals that employee engagement and work motivation each have a significant positive effect on job satisfaction, while organizational culture has an insignificant negative impact. Simultaneously, these three variables together influence job satisfaction. Novelty: This study contributes new insights by highlighting the differing effects of organizational culture versus engagement and motivation, emphasizing that strong engagement and motivation drive satisfaction even when organizational culture does not. Implications: The findings suggest that improving employee engagement and fostering work motivation should be prioritized in management strategies to enhance overall job satisfaction, while organizational culture may require re-evaluation to better align with employee satisfaction objectives.